Parental feeding knowledge, practices and Chinese children and adolescents' weight status. Issue 4 (2nd October 2021) - Zhang, Li; Zhang, Yaorong; Qiu, Liya; Yang, Guangxing; Jiang, Haiyan; Zheng, Mengyi; Wang, Jie
ABSTRACT: Childhood obesity is related to impaired health and to some diseases in adulthood. Overweight children and adolescents have also been shown to experience social and psychological problems such as stigmatization and poor self-esteem. Thus, it is imperative to investigate the determinants of children and adolescents' weight outcomes. Through analyzing the 2004, 2006, 2009 and 2011 waves of survey data released by China Health and Nutrition Survey (CHNS), this paper studied how parental feeding knowledge and practices have impacted the weight status of Chinese children and adolescents aged 6 to 17. The paper focused on exploring how such impacts varied by parental gender and rural-urban residence. Logistic regression was used to conduct the analyses. The results showed that parental feeding knowledge and practices varied by gender and by rural-urban residence. Specifically, food preferences, energy intake (such as carbohydrate, protein and fat intake) and numbers of meals sharing with children showed different patterns among mothers and fathers. Maternal intervention on children and adolescents' eating and physical activities, parental energy intakes and meal sharing also showed rural and urban differences. The results further highlighted that the ways in which parental feeding knowledge and practices influenced children and adolescents' weight status also differed by parental gender and residence. Mothers were "gatekeepers" of children and adolescents' food choices and selection; their feeding practices played a more decisive role when influencing Chinese youth's weight status.